Beneficiômetro da Seguridade Social: Um panorama da previdência social brasileira a partir de indicadores clássicos - Graziela Ansiliero; Fábio Monteiro Vaz; Geraldo Andrade da Silva Filho; Leonardo Alves Rangel; Rogério Nagamine Costanzi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The purpose of this work is to provide an overview of social security, which, along with public health and social assistance, constitutes social security in Brazil. This text represents only a part of a trilogy of Discussion Papers structured to highlight the relevance of social security, focusing on its direct and indirect benefits and services to citizens, and the challenges for the consolidation of its three systems - health, pension, and social assistance - as the foundations of the social protection policy in the country. We have chosen a scope that prioritizes the overall public pension protection, encompassing its contributory components (public service social security systems, social protection systems for military personnel, and the urban beneficiaries of the General Social Security System - urban RGPS), semi-contributory (rural beneficiaries of the RGPS), and non-contributory (continuous payment social assistance benefits). We begin with the presentation of a set of classic indicators to structure the analysis of public social security around seven fundamental dimensions: i) the scale of the social and pension protection system; ii) coverage of social and pension protection in the population; iii) adequacy of pension benefits; iv) (simulated) effects of pension and welfare benefits on poverty; v) the contribution of pension and welfare benefits to income inequality; vi) contributory sustainability of pension systems; and vii) revenues, expenses, and pension results. The analysis points to long-term challenges but also reveals current results in terms of social protection from a pension perspective.
Keywords: H55; 330; benefit meter; social security; pension system; indicators; social protection